2018
DOI: 10.1097/ruq.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Thyroid, Submandibular, and Parotid Glands Elasticity With Shear-Wave Elastography in Children

Abstract: Tissue elasticity is becoming a more commonly used parameter in evaluation of parenchyma in inflammatory diseases. Considering the changes in the thyroid and salivary glands with adolescence, determination of mean elasticity ranges with a function of age is necessary to apply ultrasound elastography more widely in the pediatric population.The thyroid, submandibular, and parotid glands of 127 healthy volunteers (66 males, 61 females; mean age = 10.3 ± 3.9 years; range = 3-17 years) were evaluated with shear-wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
5
7
1
Order By: Relevance
“…Submandibular gland strain index has not been investigated compared to periglandular soft tissues in children. As comparable with our results, the mean elasticity values by SWE in children for the thyroid, submandibular, and parotid glands were reported to be 14.6±3.3 kPa, 11.8±2.2 kPa, and 11.8±2.6 kPa, respectively (17). In a recent study for parotid gland SWE, mean elasticity was found to be 9 kPa in a healthy pediatric population (18).…”
Section: Discussionsupporting
confidence: 91%
“…Submandibular gland strain index has not been investigated compared to periglandular soft tissues in children. As comparable with our results, the mean elasticity values by SWE in children for the thyroid, submandibular, and parotid glands were reported to be 14.6±3.3 kPa, 11.8±2.2 kPa, and 11.8±2.6 kPa, respectively (17). In a recent study for parotid gland SWE, mean elasticity was found to be 9 kPa in a healthy pediatric population (18).…”
Section: Discussionsupporting
confidence: 91%
“…and Badea et al . 1517 There were no correlations between anthropometric parameters and the shear moduli of the SMGs in the present study, except for BMI, which positively correlated with the shear modulus of the right SMG.…”
Section: Discussioncontrasting
confidence: 71%
“…In addition, in contrast to our study, they did not find any correlation between age, thyroid gland volume and body mass index. Arioz Habibi et al (20) reported that SWV values of the thyroid gland were significantly higher in the 13 to 17 years age group and that there was a significant positive correlation between age and SWV values. These authors explained this finding as a function of age elasticity values of the thyroid which do not show a significant difference up to 12 years of age.…”
Section: Discussionmentioning
confidence: 98%